Comparison of linezolid regimens, in addition to bedaquiline and pretomanid, for the management of drug-resistant tuberculosis (the ZeNix study): Critical reading - Zela-Coila, Frank (2023)
Presentation: In this article we present our critical appraisal of a randomized clinical trial published in the New England Journal of Medicine in 2022. Study conclusions: The study compares four linezolid regimens (in addition to bedaquiline and pretomanid) for the management of drug-resistant tuberculosis. Finally, it shows that the regimen of 600 mg of linezolid for 26 weeks had less frequency of therapeutic failure and adverse events (compared to giving it for fewer weeks or at higher doses). Critical comment: The article is relevant because the appropriate dose of linezolid and duration of treatment with this agent to minimize adverse effects and maintain efficacy against highly resistant tuberculosis is still unclear. Despite some limitations such as low number of participants, high loss to follow-up, and no statistical comparisons between groups, the results are relatively reliable for decision making.